The Therapeutic Effect of Zinc Sulfate in Iranian Neonates With Hyperbilirubinemia: A Systematic Review and Meta-Analysis - Gholamreza Kalvandi; Mehdi Shokri; Hamed Tavan (Mazandaran University of Medical Sciences, 2020)
Background: Physiologic jaundice in neonates usually occurs during the first week of life. The main cause of this condition is increased serum bilirubin due to heme catabolism. Objectives: This systematic review and meta-analysis study aimed to investigate the therapeutic effect of zinc sulfate in Iranian newborns with hyperbilirubinemia. Methods: This review was performed based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol. The databases of ISI, Cochrane Library, Google Scholar, PubMed, and Scopus were independently searched by two researchers using MeSH keywords. We included the studies published in different regions of Iran from 2015-2018. The obtained data were analyzed using the meta-analysis technique and STATA. To determine the heterogeneity across the studies, the Q and I square (I2) indices were used. Results: A total of 40 articles were collected from which 5 studies with adequate quality entered the systematic review process. The collected results were assessed in the intervention (zinc sulfate recipients) and control (without zinc sulfate treatment) groups. After the first day of consumption, total serum bilirubin level decreased 4.46 mg/dL (I2=61.9%, P=0.049) and 4.08 mg/dL (I2=72.9%, P=0.011) in the intervention and comparison groups, respectively. In the second and third days, the mean values of decreases in serum bilirubin reached 7.64 mg/dL and 6.66 mg/dL in the intervention and comparison groups, respectively. From the third day onward, serum bilirubin dropped by 8.46 and 7.08 mg/dL in intervention and control groups, respectively. Meta-regression analysis data based on the sample size and year of the study indicated a significant growing trend in using zinc sulfate by increasing years and sample size. Conclusions: Zinc sulfate is a safe and effective medication in reducing bilirubin level and its usage has increased in recent years. Therefore, this supplement could be used for the treatment of neonatal hyperbilirubinemia.